Quantitative Assessment of Job Satisfaction and Organizational Commitment Among Employees in the Banking Sector - Dangol, Ashma; Gurung, Sagun; Subedi, Sabina; Gurung, Amisha (Nepalese Journal of Management and Technology, 2025)
This study investigates the relationship between job satisfaction and organizational commitment in Nepal’s private banking sector, with the objective of identifying key job-related factors influencing employees’ emotional and psychological attachment to their organizations. A quantitative, cross-sectional research design was adopted, and primary data were collected from 250 employees working in private banks across Nepal using a structured questionnaire. Job satisfaction was measured using Spector’s Job Satisfaction Survey encompassing nine dimensions, while organizational commitment was assessed through Meyer and Allen’s three-component model. Descriptive statistics and correlation analysis were employed to examine the strength and direction of relationships between the study variables. The findings indicate that satisfaction with co-workers, effective organizational communication, and the nature of work exhibit a strong and positive association with affective commitment, highlighting the role of supportive work environments and meaningful job roles. Conversely, promotion opportunities and operating procedures recorded comparatively lower satisfaction levels, signaling critical areas for managerial intervention. The study offers practical insights for HR policy formulation and contributes context-specific empirical evidence to the Nepalese banking literature.